PENGARUH KIPAS TERHADAP WAKTU DAN LAJU PENGERINGAN MESIN PENGERING PAKAIAN - P K Purwadi; Wibowo Kusbandono (Teknoin, 2016)
The purpose of this research, in addition to design and assemble clothes dryers, as well as to determine the influence of the fan in the space of clothes dryers with respect to the time required for drying clothes and the rate of drying clothes, with initial conditions wet clothes different i.e the results of squeeze of hand and the results of squeeze of washing machine. Research carried out on the clothes dryer that works with electric energy sources and using the vapor compression cycle. Total electric power required is 2,588 kW. The clothes dryer works to get dry air at a high enough temperature that can be used for drying clothes. The clothes dryer works with open systems, meaning that the air which has been used for drying clothes immediately dumped out of the clothes dryer. The working fluid used in drying clothes is the outdoor air, whereas the working fluid that is used for the vapor compression cycle is R134a. The research was conducted by using 50 batik clothes from Pekalongan, size XL, which has a total dry weight of 7660 grams. Research results: (a) the clothes dryer can work well without a jam occurs during machine work, when no load, the air condition in the space of clothes dryers has a dry bulb temperature 72Â°C and wet bulb temperature 29.3oC (b ) for the initial conditions of the wet clothes outcome of squeeze of hand, the presence of the fan working in the space of clothes dryers is able to shorten the drying time of the clothes about 40% and can increase the rate of drying clothes about 67% (b) for the initial conditions of the wet clothes outcome of squeeze of washing machine, the presence of fan working in the space of clothes dryers is able to shorten the drying time of clothes approximately 39% and can increase the drying rate of about 65%.